2021
DOI: 10.48550/arxiv.2103.15669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A consistent two-skyrmion configuration space from instantons

Chris Halcrow,
Thomas Winyard

Abstract: To study a nuclear system in the Skyrme model one must first construct a space of low energy Skyrme configurations. However, there is no mathematical definition of this configuration space and there is not even consensus on its fundamental properties, such as its dimension. Here, we propose that the full instanton moduli space can be used to construct a consistent skyrmion configuration space, provided that the Skyrme model is coupled to a meson. Each instanton generates a unique skyrmion and we reinterpret th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…. This phenomenon is known to exist in the 1 + 1 sector [20], but this is the first time it has been observed for higher charges.…”
Section: Large and Small |R| Limitsmentioning
confidence: 66%
See 1 more Smart Citation

ADHM skyrmions

Cork,
Halcrow
2021
Preprint
Self Cite
“…. This phenomenon is known to exist in the 1 + 1 sector [20], but this is the first time it has been observed for higher charges.…”
Section: Large and Small |R| Limitsmentioning
confidence: 66%
“…Inspired by the holographic model of Sakai-Sugimoto [19], Sutcliffe showed that the standard Skyrme model is the first term in an infinite series of Skyrme models coupled to towers of vector mesons. Recently, it was conjectured that the full moduli space of instantons can be understood as low energy modes of a skyrmion, provided at least one vector meson is included in the Skyrme theory [20].…”
Section: Introductionmentioning
confidence: 99%

ADHM skyrmions

Cork,
Halcrow
2021
Preprint
Self Cite
“…On top of its phenomenological successes, a beautiful advantage of Sutcliffe's model is how it explains the accuracy of the Atiyah-Manton approximation [28] of Skyrme fields from Yang-Mills instantons; the holonomy of instantons on R 4 well-approximate skyrmions, and Sutcliffe's model provides a solid theoretical framework for controlling how good the approximation is. This relationship with instantons also allows for a consistent configuration space on which to study low-energy interactions of skyrmions [29,30].…”
Section: Introductionmentioning
confidence: 98%
“…On top of its phenomenological successes, a beautiful advantage of Sutcliffe's model is how it explains the accuracy of the Atiyah-Manton approximation [28] of Skyrme fields from Yang-Mills instantons; the holonomy of instantons on R 4 well-approximate skyrmions, and Sutcliffe's model provides a solid theoretical framework for controlling how good the approximation is. This relationship with instantons also allows for a consistent configuration space on which to study low-energy interactions of skyrmions [29,30].…”
Section: Introductionmentioning
confidence: 99%